Agricultural Use of Copper and Its Link to Alzheimer’s Disease - Coelho, Fábio C. (Biomolecules, 2020)
Copper is an essential nutrient for plants, animals, and humans because it is an indispensable component of several essential proteins and either lack or excess are harmful to human health. Recent studies revealed that the breakdown of the regulation of copper homeostasis could be associated with Alzheimer’s disease (AD), the most common form of dementia. Copper accumulation occurs in human aging and is thought to increase the risk of AD for individuals with a susceptibility to copper exposure. This review reports that one of the leading causes of copper accumulation in the environment and the human food chain is its use in agriculture as a plant protection product against numerous diseases, especially in organic production. In the past two decades, some countries and the EU have invested in research to reduce the reliance on copper. However, no single alternative able to replace copper has been identified. We suggest that agroecological approaches are urgently needed to design crop protection strategies based on the complementary actions of the wide variety of crop protection tools for disease control.